THE BOSNIAN ISLAMIC COMMUNITY AND ITS POSITION ON INTER-RELIGIOUS DIALOGUE, INTERNATIONAL LAW, AND THE NATURE OF BOSNIAN SOCIETY - Alibašić, Ahmet (Scriptura, 2020)
This essay presents and discusses The Platform of the Islamic Community in Bosnia and Herzegovina for Dialogue (2006), a programmatic document of the Islamic Community in Bosnia and Herzegovina. Its first section sets out basic principles for Bosnian Muslim participants in inter-religious dialogue on religious diversity and coexistence. The second one deals with inter-ethnic and international relations, human rights, and violence. The third section highlights the Bosnian Muslim perspective on the 1991-1995 war in Bosnia and Herzegovina and the post-war restoration of a pluralist society. The Platform offers a rare but clear statement of the Islamic Community’s position on dialogue and cooperation and was reasonably positively received by Christian theologians in the region.